PENINGKATAN POLA PIKIR PETANI KANGKUNG DARAT MELALUI PENYULUHAN DAN ANALISIS USAHATANI (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2022)
Ipomoea reptans L. is ones type of vegetable that is consumed by the people of Gorontalo. The Mo’awota farmer group harvests every day. The obstacle faced is the lack of knowledge about organic cultivation and farming analysis so that farmer do not know the amount of income obtained from their farming. The purpose of this activity is to increase farmers’ knowledge about the importance of farming analysis and pest control proper and enviromentally friendly farming so as to production that is safe for consumers. The activity was by providing counseling in the Mo’awota farmer group Bulango Timur and conducting pree tests, post tests and calculating farming analysis. The results show that there is increase in farmers’ knowledge about organic farming and pest and desease control. The results of farming analysis obtained that the average income each farmer is Rp.1.060.000,-/month and R/C ratio of 2,12.